2021
DOI: 10.3390/molecules26072083
|View full text |Cite
|
Sign up to set email alerts
|

Strength of the [Z–I···Hal]− and [Z–Hal···I]− Halogen Bonds: Electron Density Properties and Halogen Bond Length as Estimators of Interaction Energy

Abstract: Bond energy is the main characteristic of chemical bonds in general and of non-covalent interactions in particular. Simple methods of express estimates of the interaction energy, Eint, using relationships between Eint and a property which is easily accessible from experiment is of great importance for the characterization of non-covalent interactions. In this work, practically important relationships between Eint and electron density, its Laplacian, curvature, potential, kinetic, and total energy densities at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 148 publications
1
16
0
Order By: Relevance
“…Further, this study experimentally demonstrated that the chlorine bonded to an electron-rich arene ligand acts as a nucleophile by donating an electron density towards the polarized chlorine coordinately bonded to the central Zn metal cation (Figure 5b). The experimental observations are recently further corroborated by several theoretical studies based on the topological analysis [52,53].…”
Section: Halogen Bondssupporting
confidence: 61%
See 1 more Smart Citation
“…Further, this study experimentally demonstrated that the chlorine bonded to an electron-rich arene ligand acts as a nucleophile by donating an electron density towards the polarized chlorine coordinately bonded to the central Zn metal cation (Figure 5b). The experimental observations are recently further corroborated by several theoretical studies based on the topological analysis [52,53].…”
Section: Halogen Bondssupporting
confidence: 61%
“…It was shown that the positive electrostatic potentials above carbonyl carbon atoms in acetyl fluoride and acetamide correlate well with their relative tendencies towards nucleophilic substitution reactions, such as hydrolysis [80]. Both positive σ-holes and π-holes can be present in one molecule and their interactions with negative sites such as lone pairs and anions are highly directional [53,88,89].…”
Section: π-Holes Interactionsmentioning
confidence: 99%
“…Indeed, quantitative relationships have been derived in certain classes of systems and usefully applied where the binding energy can be simply related to one or more indicators derived from these methods. For example, it is common in the literature to consider the bond critical point density as a measure of bond strength [23][24][25][26][27] and possibly even with spectroscopic perturbations. 28 In an alternate scheme, the energies of some of these bonds are sometimes assessed via a simple relationship with the potential energy density 24,[29][30][31] or other quantities extracted from AIM analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The venerable H-bond serves as the template for a host of closely related noncovalent bonds. Among these, the halogen bond is the most thoroughly characterized and utilized to date. This bond arises when the bridging proton of the H-bond is replaced by a halogen atom, typically I, Br, or Cl. The H-bond and the halogen bond share many characteristics, such as the proclivity toward linearity and the mix of electrostatic, induction, and dispersion components that comprise the total interaction energy.…”
Section: Introductionmentioning
confidence: 99%